2010
DOI: 10.1016/s1028-4559(10)60006-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Offspring Sex Ratio Between Cleavage Stage Embryo Transfer and Blastocyst Transfer

Abstract: The sex ratio was influenced by cleavage stage ET and blastocyst-stage ET. In both cases, there was a bias towards males. In addition, when blastocyst ET was compared with day 3 ET, there was no further increase in the percentage of male offspring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 17 publications
1
5
0
2
Order By: Relevance
“…To our knowledge, this is the first report comparing the offspring sex ratio between fresh BTs and vitrification-thawed BTs (21). Our previous study also indicated similar trends in favor of higher numbers of male offspring after embryo transfer after day 3 culture and after day 5 sequential blastocyst culture.…”
supporting
confidence: 73%
“…To our knowledge, this is the first report comparing the offspring sex ratio between fresh BTs and vitrification-thawed BTs (21). Our previous study also indicated similar trends in favor of higher numbers of male offspring after embryo transfer after day 3 culture and after day 5 sequential blastocyst culture.…”
supporting
confidence: 73%
“…Our previous data show a similar trend in favor of a higher number of male offspring following ET after day 3 culture and day 5 sequential blastocyst culture. However, the overall female-to-male ratio of offspring resulting from day 3 embryos was not significantly different from the ratio of offspring resulting from blastocyst transfer (46). We suspect that male-biased sex ratio is the result of selective ET favoring the top-quality embryos on fresh transfer (47).…”
Section: Discussionmentioning
confidence: 76%
“…Certaines ne mettent pas en é vidence de diffé rence significative de dé viation du sex-ratio vers le sexe mâle aprè s transfert au stade blastocyste par comparaison avec des embryons pré coces [18,[29][30][31] ou la population gé né rale [32]. En revanche, d'autres é tudes rapportent une dé viation significative du sexratio vers la progé niture masculine aprè s transfert au stade blastocyste en prenant en ré fé rence soit des embryons pré coces [13,14] soit la population gé né rale [12,15,16]. Dans notre é tude, le sex-ratio n'est pas significativement diffé rent entre le groupe blastocyste et le groupe té moin (embryons j2) (respectivement 1,08 versus 0,96).…”
Section: Discussionunclassified
“…À l'heure actuelle, toutes les é tudes ayant comparé le transfert frais d'un blastocyste avec celui d'un embryon pré coce (j2/j3) ont observé une efficacité accrue du transfert diffé ré [9][10][11]. Cependant, certains travaux ont soulevé des questions posé es par le transfert au stade blastocyste : une dé viation du sex-ratio vers la progé niture mâle a é té observé e aprè s transfert au stade blastocyste [12][13][14][15][16] ; il a é té dé crit, il y a quelques anné es, que la culture in vitro d'embryons ovins et bovins é tait associé e à la naissance de progé nitures mâles obè ses (« syndrome du gros veau ») avec quelquefois des anomalies de carcasse (croissance pré natale anormale et taux accru de malformations congé nitales) [17] ; peu de donné es sont disponibles sur le dé roulement de la grossesse et l'é tat des enfants né s aprè s transfert au stade blastocyste et elles sont, le plus souvent, issues de cohortes hé té rogè nes mêlant grossesses uniques et grossesses multiples [18,19]. L'objectif de ce travail ré trospectif é tait d'analyser le devenir de la grossesse, le dé roulement de l'accouchement et l'é tat des enfants à la naissance (selon les informations disponibles sur les fiches grossesse FIVNAT collecté es au CHRU de Tours) au sein d'une population homogè ne de grossesses uniques en comparant les transferts tardifs (j5/j6) aux transferts embryonnaires pré coces (j2).…”
Section: Introductionunclassified